Neurogenesis Recovery Induced by Granulocyte-colony Stimulating Factor in Neonatal Rat Brain After Perinatal Hypoxia - Yung-Ning Yang; Chien-Seng Lin; Chun-Hwa Yang; Yu-Hung Lai; Pei-Ling Wu; San-Nan Yang (Elsevier, 2013)
Perinatal hypoxia can lead to a wide range of neurological deficits depending on the differential vulnerability of the involved brain regions to oxygen deprivation. It remains unclear whether the differential vulnerability to oxygen deprivation leads to altered neurogenesis in the neonatal brain after perinatal hypoxia. The primary objective was to investigate whether perinatal hypoxia induces deleterious changes in neurogenesis within three representative brain regions (dentate gyrus of the hippocampus, midbrain, and temporal cortex), with regards to common pathological areas clinically. The secondary objective was to investigate whether granulocyte-colony stimulating factor (G-CSF) therapy exerts beneficial effects in neurogenesis in neonatal rat brains subjected to experimental perinatal hypoxia. Materials and methods: Rat pups were subjected to experimental perinatal hypoxia on the tenth day of life (P10). They were then given G-CSF (30 μg/kg, single injection/day, intraperitoneal injection, P11-16). The neurogenesis efficacy was analyzed on P17 and the radial-arm maze task, a memory task for higher cognitive functions such as problem-solving abilities, was evaluated on P37-58. Results: Perinatal hypoxia caused a significant decrease in neurogenesis within the three representative brain regions, and this deleterious outcome was alleviated by G-CSF (p < 0.05). In addition, the G-CSF therapy markedly improved the decreased performance of long-term cognitive functions induced by perinatal hypoxia (p < 0.05). Conclusion: This study suggests that G-CSF may be a potentially beneficial therapy, at least in part, through universal recovery of neurogenesis effects in the neonatal brain after perinatal hypoxia insult.